PENGARUH KOMUNIKASI DAN MOTIVASI KERJA SERTA KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI DAN KINERJA KARYAWAN DINAS PENGELOLA KEUANGAN DAERAH KABUPATEN LUMAJANG - Roshiful Aqli Qosyim (RELASI : JURNAL EKONOMI, 2014)
The study, entitled "Effect of Communication And Motivation And Job Satisfaction and Organizational Commitment Against Employee Performance Regional Financial Management Office Lumajang", aims to analyze the influence of communication on organizational commitment, job motivation to analyze the influence of organizational commitment, analyzing the effect of job satisfaction on organizational commitment, analyze the influence of communication on the performance of employees working, analyze the influence of work motivation on employee performance, analyzing the effect of job satisfaction on employee performance, analyzing the influence of organizational commitment on employee performance against the Department of Regional Financial Management Lumajang, population in this study were all employees/ employees Dinas business Regions Financial Lumajang numbering 108 people (2013 Annual Report of the Office of Regional Financial Management Lumajang). Sampling technique in this study using Startified proportionate random sampling based on title/ rank. The method used was a survey method to research the type of explanation or explanatory research. The analysis model used in this study is the Structural Equation Modeling (SEM). From the study results showed that the positive effect of communication variables on organizational commitment of 0.182, work motivation has a positive effect on organizational commitment was 0,276, job satisfaction has a positive effect on organizational commitment of 0.414, communication has a positive effect on employee performance by 0.251, work motivation has a positive effect on performance employees amounted to 0.251, job satisfaction has a positive effect on employee performance by 0.409, organizational commitment has a positive effect on the performance of employees is 0.175.